Moderasi Beragama sebagai Landasan Dakwah Menuju Kehidupan Rukun di Suku Talang Mamak Indragiri Hulu Provinsi Riau - Muhammad Ilham (Syntax Idea)
The Talang Mamak tribe in Indragiri Hulu, Riau, is an indigenous community with a traditional belief system. Islamic da'wah in this community requires a balanced and wise approach, which is religious moderation. This article aims to explain the role of religious moderation as the foundation of effective da'wah in creating harmonious living within the Talang Mamak community. A moderate approach to da'wah not only respects local traditions but also fosters a harmonious relationship between Islam and indigenous wisdom. Through dialogue, respect for customs, and inclusive approaches, da'wah can serve as a means of spiritual and social transformation without causing conflict or marginalizing groups. This study uses a descriptive-analytical method to understand the importance of moderation in da'wah within traditional communities such as the Talang Mamak tribe.